The Narrator and the Meaning: A Reading of “The Kiss” by Isaac Babel Compared to Alexander Pushkin’s “The Postmaster” - Танхилевич, Александр (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2022)
In this article, a connection between Pushkin’s The Postmaster and Babel’s The Kiss is demonstrated. The links between the stories go far beyond the general likeness of the plot, which follows the pattern of Nikolai Karamzin’s Poor Liza. This makes it possible to speak about a contrast between the narrators of Babel’s and Pushkin’s short stories. Babel’s narrator demonstrates a lack of interest in meaning – a fundamental category for Pushkin’s narrator, who extracts meaning from narratives he listens to. Unlike the narrator of The Postmaster, the narrator of The Kiss, who at first claims to be a representative of the intelligentsia, gives up reflection and meaning, surrenders his agency to his Cossack assistant, merges with the Cossack mass, and, in return, gets the physical love of Tomilina. A similar contrast could be traced between the narrator of The Kiss and the narrator of Red Cavalry. On the one hand, thus, The Kiss marks a change in Babel’s attitude towards his narrator; on the other hand, the story shows how the role of a thinking person in Russia has changed, according to Babel, since Pushkin. Therefore, the story constitutes a statement which could be interpreted as an ‘answer’ to The Postmaster.